2021
DOI: 10.3389/fpls.2020.602993
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-ESI-MRM/MS for Absolute Quantification and MS/MS Structural Elucidation of Six Specialized Pyranonaphthoquinone Metabolites From Ventilago harmandiana

Abstract: Pyranonaphthoquinones (PNQs) are important structural scaffolds found in numerous natural products. Research interest in these specialized metabolites lies in their natural occurrence and therapeutic activities. Nonetheless, research progress has thus far been hindered by the lack of analytical standards and analytical methods for both qualitative and quantitative analysis. We report here that various parts of Ventilago harmandiana are rich sources of PNQs. We developed an ultraperformance liquid chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Our previous study reported that the use of MS/MS spectra derived from a single collision energy may be insufficient to determine the complete fragmentation pathway of a specialized metabolite. 33 This is due to the complex structures and the stability of the fragment ions. 40 MRM Ion Selection, Specificity, Sensitivity, and Matrix Effect.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study reported that the use of MS/MS spectra derived from a single collision energy may be insufficient to determine the complete fragmentation pathway of a specialized metabolite. 33 This is due to the complex structures and the stability of the fragment ions. 40 MRM Ion Selection, Specificity, Sensitivity, and Matrix Effect.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For all of the triterpenoids, three calibration curves derived from the three sets of calibration standards resulted in different slopes, demonstrating that there was a matrix effect (Figure S5). In this regard, standard addition 33 was applied for the quantitation of triterpenoids in the mycelium and fruiting body samples.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations